The Effect of Giving a Combination of Sweet Carambola Juice and Honey on Blood Pressure in Menopausal Women - Jati, Dorotea Pili Penu (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study aimed to evaluate the effects of sweet starfruit juice and honey on blood pressure in menopausal women, hypothesizing a significant reduction in both systolic and diastolic readings. Research Design and Methodology: A pre-experimental design with pre-test and post-test assessments was used, involving 40 menopausal women from Kediri City, Indonesia. Participants consumed the juice and honey combination daily for one week. Blood pressure measurements were taken before and after the intervention. The Shapiro-Wilk test assessed data normality, and the Wilcoxon non-parametric test evaluated the significance of changes. Findings and Discussion: The study found significant reductions in blood pressure, with mean systolic decreasing from 146.25 mmHg to 133.75 mmHg and mean diastolic from 95.00 mmHg to 86.25 mmHg. The results support the hypothesis that this natural intervention effectively manages hypertension, attributed to the bioactive compounds in the juice and honey that promote cardiovascular health. Implications: The findings suggest incorporating sweet starfruit juice and honey into dietary recommendations as a complementary treatment for hypertension in menopausal women. Further research is needed to explore long-term effects, broader applicability, and comparative efficacy with other treatments.